EPISTEMOLOGI PENDIDIKAN ISLAM: (Mengurai Pendidikan Islam Sebagai Suatu Sistem Ilmu Pengetahuan) - Izza, Yogi Prana (Universitas Nahdlatul Ulama Sunan Giri, 2019)
“One of the problems of Islamic education today is the issue of dichotomy between “the relegious science” oriented to the hereafter happiness and “the non relegious science” oriented to worldly happiness. In fact, Islam does not distinguish between the two. This problem is directed from the formulation of an inaccurate Islamic education epistemology. Therefore, this paper seeks to unravel the epistemological foundation of Islamic education by discussing the essence of Islamic education, knowledge sources of Islamic education, the methodology of Islamic education and the alternative paradigm of integralism in religious sciences with non-religious sciences. The conclusion of this discussion explains that the essence of Islamic education is the process of adab cultivation, the process of transferring knowledge and the process of purification of the soul. These processes are actually related to the sources of knowledge in Islamic education, namely the five senses, ratios, intuition, and revelation (wahyu). The functions of these sources are complementary or integral. But in reality, the source of intuition, for example, has not yet gotten an adequate portion in Islamic education”.